Taxonomy and physiology of Pseudoxanthomonas arseniciresistens sp. nov., an arsenate and nitrate-reducing novel gammaproteobacterium from arsenic contaminated groundwater, India - Mohapatra, Balaram (PLoS One, 2018)
Reductive transformation of toxic arsenic (As) species by As reducing bacteria (AsRB) is a key process in As-biogeochemical-cycling within the subsurface aquifer environment. In this study, we have characterized a Gram-stain-negative, non-spore-forming, rod-shaped As reducing bacterium designated KAs 5-3(T), isolated from highly As-contaminated groundwater of India. Strain KAs 5-3(T) displayed high 16S rRNA gene sequence similarity to the members of the genus Pseudoxanthomonas, with P. mexicana AMX 26B(T) (99.25% similarity), P. japonensis 12-3(T) (98.9 0%), P. putridarboris WD-12(T) (98.02%), and P. indica P15(T) (97.27%) as closest phylogenetic neighbours. DNA-DNA hybridization study unambiguously indicated that strain KAs 5-3(T) represented a novel species that was separate from reference strains of P. mexicana AMX 26B(T) (35.7%), P. japonensis 12-3(T) (35.5%), P. suwonensis 4M1(T) (35.5%), P. wuyuanensis XC21-2(T) (35.0%), P. indica P15(T) (32.5%), P. daejeonensis TR6-08(T) (32.0%), and P. putridarboris WD12(T) (22.1%). The DNA G+C content of strain KAs 5-3(T) was 64.9 mol %. The predominant fatty acids were C(15:0) (37.4%), C(16:0) iso (12.6%), C(17:1) iso ω9c (10.5%), C(15:0) anteiso (9.5%), C(11:0) iso 3-OH (8.5%), and C(16:1) ω7c/ C(16:1) ω6c (7.5%). The major polar lipids were diphosphatidylglycerol, phosphatidyldimethylethanolamine, phosphatidylcholine, and two unknown phospholipids (PL1, PL2). Ubiquinone 8 (Q8) was the predominant respiratory quinone and spermidine was the major polyamine of the strain KAs 5-3(T). Cells of strain KAs 5-3(T) showed the ability to use O(2), As(5+), NO(3)(-), NO(2)(-), and Fe(3+) as terminal electron acceptors as well as to reduce As(5+) through the cytosolic process under aerobic incubations. Genes encoding arsenate reductase (arsC) for As-detoxification, nitrate- and nitrite reductase (narG and nirS) for denitrification were detected in the strain KAs 5-3(T). Based on taxonomic and physiological data, strain KAs 5-3(T) is described as a new representative member of the genus Pseudoxanthomonas, for which the name Pseudoxanthomonas arseniciresistens sp. nov. is proposed. The type strain is KAs 5-3(T) (= LMG 29169(T) = MTCC 12116(T) = MCC 3121(T)).